Creole cattle of Nunkini, Campeche, Mexico: A zoogenetic resource at risk - Cruz-Clemente, Guadalupe de Jesús (2024)
Introduction. Livestock farming with Creole cattle is practiced in rural areas with challenging characteristics for species management. Objective. To describe the production system and the socio-cultural and technical-economic factors affecting the production of Nunkiní Creole cattle (Bos taurus). Materials and methods. The study was conducted from November 2020 to October 2021 in nine livestock production units of Nunkiní, Calkiní municipality, Campeche, Mexico. Information was obtained from an interview form with social, cultural, technical, and economic study variables, applied to selected producers. Data were analyzed using descriptive statistics and ANOVA. Results. Livestock farming was carried out by men (100 %), with an average age of 58.44 years. The average years of experience were 34.61. Younger producers had higher levels of education and less experience, and were responsible for the production units of higher technological levels. The size of the livestock production unit ranged from five to twenty-two cattle (average of 14). Feeding management followed a transhumance scheme, with cattle being free-ranging on ejido lands and from May to December and semi-stabled from January to April, grazing on cultivated pastures and supplemented with agricultural residues. With the zootechnical management implemented by the producers, an average pregnancy rate of 83 % was achieved. The main product marketed was fresh meat in cuts and direct sale to consumers, with an average price of 2.675 USD$/kg. Conclusion. It is traditional extensive system that takes advantage of the common use of grasslands. It involves experienced but older producers, with small investments, and serves to strengthen their family economy. This activity is threatened by the lack of revaluation of Creole cattle and the introduction of exotic breeds in the area to maximize production.